GAMBARAN KELENGKAPAN PENGISIAN FORMULIR RAWAT JALAN DITINJAU DARI ASPEK HUKUM KESEHATAN DI PUSKESMAS SEMEN KABUPATEN KEDIRI TAHUN 2020 - AG Nugroho Pudji Lestarjo; Indah Susilowati; Krisnita Dwi Jayanti; Sabila Ainaya Nazilla (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
Puskesmas is health service facilities that are implementing publih health efforts and individual health effort which is also obliged to carry out a medical record. The purpose of this study was to determine the completeness of filling out outpatient forms in terms of health legal aspects at the Semen Health Center, Kediri Regency in 2020. This type of research was descriptive with a retrospective approach. Collecting data by observation and interviews. Sampling used simple random sampling, namely 10 outpatient medical record documents in 2020. The results obtained were from 10 incomplete samples (6%) which were filled in completely (4%) item incompleteness contained in the writing of the icd10 code and the signature of the officer. This is not in accordance with Permenkes number 269 year medical record and Permeneks Number 46 Year 2015 abaout Accreditation of Puskesmas Which requires that in every medical record should be named and signatures a doctor or other health workers directly providing health services. In addition fill forms a medical record complete must be filled because it will become the foundation in giving the diagnosis next and knows the way a patient. Should be done socialization fill forms outpatient done by the head of this, to avoid incompleteness fill forms outpatient.